PENGELOLAAN PEMBELAJARAN MATEMATIKA MENGGUNAKAN BUSUR DERAJAT DAN JAM UNTUK MENINGKATKAN KETERAMPILAN SISWA KELAS V SD - R. Bambang Prabowo. S (UNIVERSITAS BENGKULU, 2017)
: results of the research still many learning management Mathematical not optimize the use of props, the result is not optimal learning results. Including the measurement of learning at State Elementary School 08 Kabawetan, the two year half of the school year 2013 /2014. Subyek were students of class V are 20 students. Learning measurement degree angle with a bow and the clock is one of the props that can be used to membelajarkan angle measurement. The measures taken is the provision of individual tasks, preceded by the teacher's explanation about measuring angles by using arc media degrees and hours. Then proceed task individually followed the presentation of each individual and ends with an affirmation using a protractor or watch media, with the affirmation of a teacher terminated.